Transcatheter closure of patent ductus arteriosus: Our initial experience in University of Malaya Medical Centre - Zain, Zarin Ikmal Zan; Wan Ahmad, Wan Azman; Omar, Asma; Alwi, Mazeni (Faculty of Medicine, University of Malaya, 2000)
Six patients underwent transcatheter closure of patent ductus arteriosus (PDA) using either conventional Gianturco coils or the Amplatzer Ductal Occluder (ADO) device. All patients were females with a median age of 23.3 (range 4 to 26 years). The mean PDA size measured on the lateral aortogram was 3.81mm (range 2.3-5.83mm). Complete closure of the PDA was achieved in all patients.